2007
DOI: 10.1152/jn.01211.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neural Coding of Reward-Prediction Error Signals During Classical Conditioning With Attractive Faces

Abstract: Bray S, O'Doherty J. Neural coding of reward-prediction error signals during classical conditioning with attractive faces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
102
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 56 publications
18
102
0
Order By: Relevance
“…We suggest that this maximum familiarity is developed ontogenetically and reflects a tuning property of neurons involved in the perceptual learning of facial identities. As such, we suggest that this asymptotic value is akin to the values calculated in the Rescorla-Wagner model in reinforcement learning 13,[54][55][56][57] and the Pearce-Hall 12 algorithm in attention-based error learning, which have been shown to be effective models of other types of learning.…”
Section: Methodssupporting
confidence: 52%
“…We suggest that this maximum familiarity is developed ontogenetically and reflects a tuning property of neurons involved in the perceptual learning of facial identities. As such, we suggest that this asymptotic value is akin to the values calculated in the Rescorla-Wagner model in reinforcement learning 13,[54][55][56][57] and the Pearce-Hall 12 algorithm in attention-based error learning, which have been shown to be effective models of other types of learning.…”
Section: Methodssupporting
confidence: 52%
“…Interestingly, it appears that the ventral striatum, an area that has been frequently associated with the processing of prediction errors in individual learning (23)(24)(25)(26), was involved in processing prediction errors related to actually experienced, individual reward in our task in a conventional sense (i.e., with increasing activity to positive individual reward prediction errors) but showed the inverse coding pattern for observational prediction errors. Although our task was not presented to participants as a game situation (and the behavior of the confederate in no way affected the possibility of participants receiving reward), this inverse reward prediction error coding for the confederate's outcomes is supported by previous research highlighting the role the ventral striatum plays in competitive social situations.…”
Section: Discussionmentioning
confidence: 92%
“…This opens the possibility of separately examining neural activation during reward anticipation and in response to reward outcomes. For example, rewarding outcomes signaled by sensory cues, including cued pleasant odors (Gottfried et al, 2003) and attractive faces (Bray and O'Doherty, 2007), activate vmPFC. However, a number of studies using abstract rewards (ie, money), rather than sensory ones to measure gain outcomes, found that activation in the mPFC can be distinguished from the larger vmPFC area Knutson et al, 2003Knutson et al, , 2005Kuhnen and Knutson, 2005;Yacubian et al, 2006).…”
Section: Reward Processing In the Human Prefrontal Cortexmentioning
confidence: 99%